How Firm Characteristics Shape Earnings Quality: Evidence from Indonesian Manufacturing Firms - Handayani, Siti Nur; Syaiful, Syaiful (International Ecsis Association, 2025)
This study aims to analyze the effect of firm size, profitability, and liquidity on earnings quality in manufacturing companies within the industrial sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. Earnings quality is a multidimensional concept that reflects how reported earnings are reliable and relevant for stakeholders in making economic decisions. In this context, agency theory is the foundation to explain potential conflicts of interest between managers and shareholders in financial reporting practices. The sample was selected using a purposive sampling method based on specific criteria, and the data were analyzed using multiple linear regression. Classical assumption tests indicate that the data meet the requirements for normality, show no multicollinearity or autocorrelation, and satisfy the assumption of homoscedasticity. Regression results show that firm size does not significantly affect earnings quality (p > 0.05), while profitability and liquidity have a negative and significant effect on earnings quality (p < 0.05). The coefficient of determination (R²) of 14.1% indicates that the three independent variables explain only a small portion of the variation in earnings quality. The study's implications highlight the importance of monitoring managerial practices, particularly in companies with low profitability and liquidity, to prevent earnings manipulation and enhance investor trust. The findings also encourage regulators to strengthen financial reporting transparency policies and provide valuable insights for investors to evaluate financial statements critically.